Reinventing manufacturing and business processes through artificial intelligence - Rana, Geeta (Boca Raton : CRC Press, 2022)
"This book describes how newly emerging Artificial Intelligence (AI) technologies will provide unprecedented opportunities to penetrate technology and automation into everything we do, and at the same time, provide a huge playing field for businesses to develop newer models to capture market share. It establishes a milestone in understanding global transformational changes occurring in the manufacturing and corporate world due to AI and tries to find powerful and sophisticated solutions that will improve and streamline operations. Reinventing Manufacturing and Business Processes through Artificial Intelligence will be of interest to students, researchers, and professionals of the AI community as well as interdisciplinary researchers"--
OCLC-licensed vendor bibliographic record.
Keywords: Industry 4.0.; Production engineering; Automation; Artificial intelligence; TECHNOLOGY / Operations Research; BUSINESS & ECONOMICS / Industries / Manufacturing Industries